Perbandingan peningkatan keterampilan berpikir kritis dan kreatif siswa dengan menerapkan LKS berbasis problem solving dan inkuiri terbimbing pada materi kalor dan teori kinetik gas kelas XI SMAN 2 Padang - Afdatul Zikri; Yenni Darvina; Slivi Yulia Sari (Universitas Negeri Padang, 2020)
This study aims to discover the differences of student’s critical and creative thinking skills enhancement after application of problem-solving worksheet and guided inquiry worksheet for student on heat material and gas kinetic theory in 11th grade students in SMAN 2 Padang. The type of this research is quasi experiment with randomize only control group design. This study involved two experiment class, the first one used problem-solving worksheet and the second class used guided inquiry worksheet. Data collection technique were written test using essay question model. The assessment is based on critical and creative thinking skills indicators that’s observable. Data analysis using qualitative descriptive analysis technique. The result showed that after application, there are enhancement on critical and creative thinking skills. Problem solving class is 50% and guided inquiry class is 63%. Based on this study, it can be concluded that: first, critical and creative thinking skills of both classes were increased after the application of problem-solving worksheet and guided inquiry worksheet. Second, the average mark for critical and creative thinking skills on problem solving class is higher than guided inquiry class. Third, there are some differences in the enhancement of critical and creative thinking skills of student who used problem solving worksheet compared to guided inquiry worksheet.